Pallavar āṭci - Murukēca Mutaliyār, C., 1914- (Kaḻaka veḷiyīṭu ;, 1979)
Chronology of the Pallava kings, South Indian dynasty, who ruled the northern districts of Tamil Nadu from the 3d century to the 9th century.